Review of EPA homeland security efforts : Safe Buildings Program research implementation plan (National Academies, Press, 2003)
"The report examines the Environmental Protection Agency s three-year plan for a comprehensive response to a chemical or biological attack on a civilian or public sector facility. The report states that EPA has correctly identified the essential major research areas (detection, containment, decontamination, and disposal) but calls for an initial focus on decontamination and disposal efforts and a longer term research program."--Publisher's description